PEMANFAATAN BUBUR NANAS DALAM PEMBUATANVELVA UBI JALAR UNGU - Sholihah, Rahayu; Yusmarini, Yusmarini; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtain best ratio of purple sweet potato velva by additional of pinapple puree and preferred by the panelists. The research was conducted experimentally using a completely randomized design with five treatments and three replications. The treatments were UN1 (purple sweet potato puree 100 : pinapple puree0), UN2 (purple sweet potato puree 90: pinapple puree10), UN3 (purple sweet potato puree 70: pinapple puree30), UN4 (purple sweet potato puree 50: pinapple puree50), and UN5 (purple sweet potato puree 30: pinapple puree70). The obtained data was treated the analysis of variance and Duncan New Multiple Range Testat level 5%. The best treatment in this research was UN3 (purple sweet potato puree 70: pinapple puree30) which had overrun 16.63%, pH 5.38, 8.23 minutes for the melting time, fiber content 0.34%, vitamin C 0.038 mg/100 g, and overall assessment was preferred by the panelists. Keywords: Velva, pinapple puree, and purple sweet potato puree